2022
DOI: 10.1109/access.2022.3225555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Intention for the Adoption of Artificial Intelligence-Based Robots in the University to Educate the Students

Abstract: Technology adoption is accepting, integrating, and using the latest innovative technologies in society. Artificial intelligence (AI) and robotics are changing the face of the industrial and service sectors. There is a need to change the traditional way of teaching by introducing the latest innovative methods. This study aims to measure the intention of adopting AI-based robots in the educational system of Indian universities. This study uses three theories technology acceptance model, the theory of planned beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…In addition, Roy et al (2022) showed a positive thought of both teachers and students in adopting AI in universities hence, providing an affirmative answer to their research question, "Do teacher and student attitudes impact the intention to adopt AI-based robots in the education sector?''. The use of AI was found to be helpful and accessible.…”
Section: Behavioural Intention and Adoption Of Behaviourmentioning
confidence: 90%
“…In addition, Roy et al (2022) showed a positive thought of both teachers and students in adopting AI in universities hence, providing an affirmative answer to their research question, "Do teacher and student attitudes impact the intention to adopt AI-based robots in the education sector?''. The use of AI was found to be helpful and accessible.…”
Section: Behavioural Intention and Adoption Of Behaviourmentioning
confidence: 90%
“…A pilot survey of 57 responses was conducted to test the questionnaire’s reliability. Cronbach’s alpha ( α ) values for all the items were valid and above 0.70 (Hair et al , 2014; Roy et al , 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived benefits (PB): Researchers and analysts believe that BT-engaged SC gains benefits, including progressing information sharing, cost decrease, adequacy, straightforwardness, tracking, tracing, and improving operational excellence (Roy, Babakerkhell, et al, 2022). BT-engaged SC aims to grow the association's effectiveness and reality in the market (Hassani et al, 2018;van Hoek, 2019).…”
Section: Technological Factors (Tf)mentioning
confidence: 99%